PERAN GURU PKN SEBAGAI AGEN PERUBAHAN DALAM MENUMBUHKAN BELA NEGARA PADA SISWA KELAS XI DI SMAN 1 PERCUT SEI TUAN - Cindi Nurningsih; Nadia Sasi Kirana Simatupang; Oksari Anastasya Sihaloho; Putri Syakinah; Sefi Hariati Gulu; Zhane Arnaya (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This study aims to explore the role of education in instilling the spirit of national defense among grade XI students at SMAN 1 Percut Sei Tuan. Using qualitative descriptive methods, data were collected through interviews, direct observation, and documentation. Data sources include Civic Education teachers and students, with a focus on nationalist attitudes and efforts to develop them. The results of the study indicate that education based on Pancasila values ​​is very important in building students' morals and discipline. Challenges faced include a lack of caring and responsibility, which is seen in conflicts between students. Participation in social and extracurricular activities is considered effective in fostering a sense of love for the homeland and tolerance. This study emphasizes that national defense is a shared responsibility that must be integrated into the education curriculum, to prepare a responsible and nationalistic young generation.